Research on Static Var Generator Detection Method for New Energy Fields and Stations in Hunan Area. Issue 1 (1st January 2022) - Yao, Xinrui; Sheng, Jie; Huang, Hualin; Yu, Da; Hu, Jinhao
Abstract: With the strategy of constructing new power system with new energy as the main body put forward, the installed capacity of new energy in Hunan area will usher in explosive growth during the 14th five-year Plan period. The safe and stable operation of new energy stations to power grid will also be increasingly intensified. The paper briefly introduces the working principle, working mode and application of SVG(Static Var Generator) device supporting new energy stations. Based on relevant standards, a test scheme suitable for new energy stations in Hunan province is proposed. Taking the SVG device supporting a new energy station in Hunan province as an example, the grid-connection performance test is carried out to comprehensively and scientifically evaluate the network-related performance of SVG devices in the new energy station.